Biochemical Properties of Human D-amino Acid Oxidase Variants and Their Potential Significance in Pathologies - Sacchi, Silvia; Cappelletti, Pamela; Murtas, Giulia (Frontiers in Molecular Biosciences, 2018)
The stereoselective flavoenzyme D-amino acid oxidase (DAAO) catalyzes the oxidative deamination of neutral and polar D-amino acids producing the corresponding -keto acids, ammonia and hydrogen peroxide. Despite its peculiar and atypical substrates, DAAO is widespread expressed in most eukaryotic organisms. In mammals (and humans in particular), DAAO is involved in relevant physiological processes ranging from D-amino acid detoxification in kidney to neurotransmission in the central nervous system, where DAAO is responsible of the catabolism of D-serine, a key endogenous co-agonist of N-methyl-D-aspartate receptors. Recently, structural and functional studies have brought to the fore the distinctive biochemical properties of human DAAO (hDAAO). It appears to have evolved to allow a strict regulation of its activity, so that the enzyme can finely control the concentration of substrates (such as D-serine in the brain) without yielding to an excessive production of hydrogen peroxide, a potentially toxic reactive oxygen species (ROS). Indeed, dysregulation in D-serine metabolism, likely resulting from altered levels of hDAAO expression and activity, has been implicated in several pathologies, ranging from renal disease to neurological, neurodegenerative and psychiatric disorders. Only one mutation in DAO gene was unequivocally associated to a human disease. However, several single nucleotide polymorphisms (SNPs) are reported in the database and the biochemical characterization of the corresponding recombinant hDAAO variants is of great interest for investigating the effect of mutations. Here we reviewed recently published data focusing on the modifications of the structural and functional properties induced by amino acid substitutions encoded by confirmed SNPs and on their effect on D-serine cellular levels. The potential significance of the different hDAAO variants in human pathologies will be also discussed.